CircJARID2 Regulates Hypoxia-Induced Injury in H9c2 Cells by Affecting miR-9-5p–Mediated BNIP3. Issue 1 (July 2021) - Cai, Xinyong; Li, Bin; Wang, Yunxia; Zhu, Hongmin; Zhang, Ping; Jiang, Panpan; Yang, Xu; Sun, Jianhua; Hong, Lang; Shao, Liang
Abstract : Abstract: Myocardial infarction (MI) is a common cardiovascular disease, and many circular RNAs (circRNAs) have been found to participate in the pathological process. This study was to research circRNA jumonji and AT-rich interaction domain containing 2 (circJARID2) in MI. MI cell model was established by hypoxia treatment in H9c2 cells. CircJARID2 and microRNA-9-5p (miR-9-5p) levels were examined using real-time polymerase chain reaction. Cell viability detection was performed by Cell Counting Kit-8 (CCK-8) and 5-ethynyl-2′-deoxyuridine (Edu) assays. Cell apoptosis was evaluated by flow cytometry and caspase-3 activity assay. Apoptotic markers and B-cell lymphoma-2 (Bcl-2) interacting protein 3 (BNIP3) were quantified by western blot. Inflammatory cytokines were determined via enzyme-linked immunosorbent assay. The genic interaction was analyzed through dual-luciferase reporter and RNA immunoprecipitation assays. Hypoxia induced the upregulation of circJARID2 expression in H9c2 cells. The hypoxia-induced cell viability inhibition, apoptosis promotion, and inflammatory response were all counterbalanced by knockdown of circJARID2. CircJARID2 interacted with miR-9-5p, and its function in regulating the hypoxia-induced cell injury was also dependent on targeting miR-9-5p. BNIP3 acted as a target gene of miR-9-5p, and circJARID2 had positive effect on BNIP3 expression by binding to miR-9-5p. MiR-9-5p played a protective role for H9c2 cells against the hypoxia-induced injury via targeting BNIP3. CircJARID2 overexpression contributed to the hypoxia-induced H9c2 cell injury by sponging miR-9-5p to upregulate BNIP3 expression, showing a novel molecular network of MI pathomechanism. Abstract : Supplemental Digital Content is Available in the Text.